Solid-state battery and method for producing same by deprotonation

The method addresses the challenge of achieving effective contact in solid-state batteries by deprotonating a ceramic body to create a porous layer that allows metal elements to penetrate, reducing the risk of lithium dendrite formation and enhancing battery performance.

JP7671800B2Active Publication Date: 2025-05-02THE SWATCH GRP RES & DEVELONMENT LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023057171
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-04-08
Filing Date
2023-03-31
Publication Date
2025-05-02
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

Solid-state batteries face challenges in achieving effective contact between the anode and the solid electrolyte, leading to potential lithium dendrite formation and short circuits, which existing solutions like liquid electrolytes cannot fully address due to leakage risks.

Method used

A method for producing solid-state batteries involves protonating a ceramic body to form a protonated layer, deprotonating it to create a porous layer with small cavities, allowing metal elements to penetrate and improve contact with the solid electrolyte, thereby reducing the risk of dendrite formation.

Benefits of technology

The method enhances the contact area between the metal electrode and the solid electrolyte, reducing the risk of lithium dendrite formation and improving the overall performance and safety of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671800000001
    Figure 0007671800000001
  • Figure 0007671800000002
    Figure 0007671800000002
  • Figure 0007671800000003
    Figure 0007671800000003
Patent Text Reader

Abstract

To provide a method for producing a solid-state battery which improves the contact between an anode and a solid electrolyte, without the use of a liquid contact element.SOLUTION: The present invention relates to a solid-state battery 20 including a solid electrolyte 8 and a production method thereof. The method includes the following successive steps: a step 1 of protonating a body 11 containing, preferably being entirely made of, a protonatable ceramic material, to form a protonated layer 13 on the body; a step 3 of deprotonating the protonated layer so as to obtain a porous layer provided with mini-cavities 18; a step 4 of depositing a metal element forming an anode 14 on the deprotonated layer on a first side 7 of the body, and of infiltrating the mini-cavities of the porous layer with the metal element; and a step 5 of assembling a cathode 15 on a second side 9 of the body, preferably opposite the first side of the anode.SELECTED DRAWING: Figure 2f
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to solid-state batteries, and also to "all-solid-state batteries".

[0002] The present invention further relates to a method for producing such a solid-state battery.

[0003] The invention further relates to an electronic system, such as a watch, a laptop computer, a mobile phone or an automobile, that includes such a solid-state battery. [Background technology]

[0004] Solid-state or all-solid-state batteries are an alternative to lithium-ion batteries. Unlike lithium-ion batteries, which contain a liquid electrolyte, solid-state batteries have a solid electrolyte between the anode and cathode.

[0005] Such batteries have the advantage of having a higher energy density and therefore a larger storage capacity than lithium-ion batteries, which makes them promising for many applications.

[0006] Ceramic compounds such as LLZO compounds are known for use as solid electrolytes.

[0007] LLZO-based compounds have high ionic conductivity. These ceramic compounds contain lithium, lanthanum, zirconium, and oxygen, and have the chemical formula Li7La3Zr2O 12 or Li7La3Zr2O7. It can also be doped with tantalum or aluminum to stabilize these cubic phases that are conductive to lithium ions. 6.4 La3Zr2Ta 0.6 O 12 has.

[0008] One of the drawbacks of ceramic compounds is the contact between the negative electrode, for example made of lithium, and the solid electrolyte. More specifically, it is important to prevent impurities and irregularities between the two elements, since their presence can lead to current crowding and cavities, which can lead to the formation of lithium dendrites that can pass through the ceramic compound and cause a short circuit. This is because these current crowding can exceed a current threshold, which then leads to the formation of dendrites in the ceramic compound, especially lithium dendrites.

[0009] One solution to this problem is to place a conductive liquid between the ceramic compound and the lithium anode, which improves contact between the two.

[0010] However, problems arise with batteries containing liquid electrolytes, in particular the risk of the liquid leaking out of the battery and the consequences that accompany it, and even the presence of liquid does not completely avoid the risk of lithium dendrite formation. Summary of the Invention [Problem to be solved by the invention]

[0011] The object of the present invention is to overcome the aforementioned drawbacks and aims to provide a method for producing a solid-state battery that improves the contact between the negative electrode and the solid electrolyte without the use of liquid contact elements. [Means for solving the problem]

[0012] Therefore, the present invention relates to a method for producing a solid-state battery.

[0013] The present invention is notable in that the method comprises the following successive steps: - protonating a body containing, preferably consisting entirely of, a protonatable ceramic material to form a protonated layer on the body; - deprotonating the protonated layer so as to obtain a porous layer provided with small cavities; - depositing a metal element forming a negative electrode on the deprotonated layer on the first side of the body, allowing the metal element to penetrate into these small cavities of the porous layer; and - attaching a positive electrode onto a second side of the body, preferably opposite the first side of the negative electrode.

[0014] The removal of protons by a step of deprotonating the protonated layer creates small cavities in the layer, which make it porous, in part so that the metal elements forming the negative electrode can easily penetrate into the porous layer, especially in the molten state. The penetration of the negative electrode into the electrolyte improves the contact between the metal elements and the bulk of the solid electrolyte, in particular because the contact area is significantly increased by the cavities in the porous layer. Furthermore, the risk of current crowding and therefore the formation of dendrites in the non-protonated parts is prevented.

[0015] Thus, the risk of lithium dendrite formation is reduced.

[0016] According to a particular embodiment of the invention, the ceramic material is selected from: - doped or undoped lithium and / or lanthanum zirconium oxides of the LLZO system, - doped or undoped β-alumina solid electrolyte materials of the Na-b''-Al2O3 system; - ternary or quaternary or higher sulfide-based solid electrolyte materials, for example of the Li6PS5X system (X being selected from the elements Cl, Br or I) or the Li2S-P2S5 system, - Ternary or quaternary or higher halogen-based solid electrolyte materials, for example, Li3MX6-based (where M is a metal or metal alloy and X is a halogen); - LISICON (lithium superionic conductor) system, e.g. Li 4±x S 1-x X x Lithium ion conducting solid electrolyte materials based on O4 (X is selected from the elements P, Al, or Ge), and - NASICON (sodium superionic conductor) system, e.g. Nax A sodium ion conducting solid electrolyte material in the MM'(XO4)3 system (wherein M and M' are metals and X is selected from the elements Si, P, or S).

[0017] According to certain embodiments of the invention, the protonation step involves immersing the body in a protic or acidic solvent, such as water, acetone, mineral oil, or ethanol.

[0018] According to a particular embodiment of the invention, the deprotonation step involves heating the body to a predetermined temperature, preferably above 750° C., to separate the protons from the protonated layer.

[0019] According to a particular embodiment of the invention, the metal elements are melted onto the body during the metal element deposition step.

[0020] According to a particular embodiment of the invention, the metallic element comprises a material selected from the following: - Alkali metals such as lithium, sodium, potassium, rubidium, cesium, or francium, - alkaline earth metals such as beryllium, magnesium, calcium, strontium, barium, or radium, - all transition metals from groups 3 to 11 of the periodic table, including the lanthanides and actinides, - Alloys of these metals.

[0021] According to certain embodiments of the invention, the method includes the additional step of removing a portion of the protonated layer from the body in order to laminate the positive electrode directly onto the non-protonated portion of the body.

[0022] According to a particular embodiment of the invention, the additional step of removing a portion of the protonated layer from the body is performed by polishing the second side of the body.

[0023] According to a particular embodiment of the invention, the positive electrode contains a material selected from the following: - LiNi x Mny Co z O2 or Li 2-x-y-z Ni x Mn y Co z Lithium nickel manganese cobalt oxide (NMC) such as O2, where x+y+z≦1, - LiNi 0.5 Mn 1.5 Lithium nickel manganese oxide (LNMO) such as O4, - Lithium iron phosphate (LFP) such as LiFePO4, - LMO-based lithium manganates such as LiMn2O4, and - NCA-based lithium nickel cobalt aluminum oxides such as LiNiCoAlO2.

[0024] The present invention further relates to a solid-state battery comprising an anode, a cathode, and a ceramic solid electrolyte, the solid electrolyte being provided with a porous deprotonated layer having small cavities and a non-protonated portion adjacent to each other, the cathode being laminated on the body, and the anode comprising a metal element disposed on the porous deprotonated layer of the body on the opposite side to the cathode, the metal element penetrating the small cavities of the porous deprotonated layer.

[0025] According to a particular embodiment of the invention, the metal element is blocked by a non-protonated portion of the body.

[0026] According to a particular embodiment of the invention, the metallic element comprises a material selected from the following: - Alkali metals such as lithium, sodium, potassium, rubidium, cesium, or francium, - alkaline earth metals such as beryllium, magnesium, calcium, strontium, barium, or radium, - all transition metals from groups 3 to 11 of the periodic table, including the lanthanides and actinides, - Alloys of these metals.

[0027] According to a particular embodiment of the invention, the ceramic material is selected from: - doped or undoped lithium and / or lanthanum zirconium oxides of the LLZO system, - doped or undoped β-alumina solid electrolyte materials of the Na-b''-Al2O3 system; - ternary or quaternary or higher sulfide-based solid electrolyte materials, for example of the Li6PS5X system (X being selected from the elements Cl, Br or I) or the Li2S-P2S5 system, - Ternary or quaternary or higher halogen-based solid electrolyte materials, for example, Li3MX6-based (where M is a metal or metal alloy and X is a halogen); - LISICON (lithium superionic conductor) system, e.g. Li 4±x S 1-x X x Lithium ion conducting solid electrolyte materials based on O4 (X is selected from the elements P, Al, or Ge), and - NASICON (sodium superionic conductor) system, e.g. Na x A sodium ion conducting solid electrolyte material in the MM'(XO4)3 system (wherein M and M' are metals and X is selected from the elements Si, P, or S).

[0028] According to a particular embodiment of the invention, the positive electrode is attached to the unprotonated portion of the body.

[0029] According to a particular embodiment of the invention, the positive electrode contains a material selected from the following: - LiNi x Mn y Co z O2 or Li 2-x-y-z Ni x Mn y Co z Lithium nickel manganese cobalt oxide (NMC) such as O2, where x+y+z≦1, - LiNi 0.5 Mn 1.5 Lithium nickel manganese oxide (LNMO) such as O4, - Lithium iron phosphate (LFP) such as LiFePO4, - LMO-based lithium manganates such as LiMn2O4, and - NCA-based lithium nickel cobalt aluminum oxides such as LiNiCoAlO2.

[0030] The invention further relates to an electronic system comprising such an all-solid-state battery, such as a watch, a drone, a laptop computer, a mobile phone, or an automobile.

[0031] Other specific features and advantages will be clearly observed in the following description, given as a general guide and in no way as a limiting guide, with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0032] [Figure 1] FIG. 2 is a block diagram showing steps of the method according to the present invention; [Figure 2a] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2b] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2c] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2d] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2e] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. [Figure 2f] 1A-1D are schematic cross-sectional views of a battery after each step in a method of producing a battery according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] The present invention relates to a method 10 for producing a solid-state battery 20. Such a battery 20 includes an anode 14, a cathode 15, and an electrolyte disposed between the cathode 15 and the anode 14. Solid-state electrolyte 8 is understood to refer to an electrolyte that is not a liquid.

[0034] The electrolyte 8 is formed from a body 11 containing a material that can be protonated. + It is possible to perform ion exchange, and preferably the body 11 is made entirely of this material.

[0035] The ceramic material used can be selected from the following: - doped or undoped lithium and / or lanthanum zirconium oxides of the LLZO system, - doped or undoped β-alumina solid electrolyte materials of the Na-b''-Al2O3 system; - ternary or quaternary or higher sulfide-based solid electrolyte materials, for example of the Li6PS5X system (X being selected from the elements Cl, Br or I) or the Li2S-P2S5 system, - Ternary or quaternary or higher halogen-based solid electrolyte materials, for example, Li3MX6-based (where M is a metal or metal alloy and X is a halogen); - LISICON (lithium superionic conductor) system, e.g. Li 4±x S 1-x X x Lithium ion conducting solid electrolyte materials based on O4 (X is selected from the elements P, Al, or Ge), and - NASICON (sodium superionic conductor) system, e.g. Na x A sodium ion conducting solid electrolyte material in the MM'(XO4)3 system (wherein M and M' are metals and X is selected from the elements Si, P, or S).

[0036] The ceramic material is preferably made entirely of this material.

[0037] Preferably, LLZO based compounds are selected because they have high ionic conductivity.

[0038] To produce the battery 20, a method is used that includes a first step 1 of protonating the ceramic body 11. To replace the atoms of the ceramic with protons, the body 11 is immersed in a protic or acidic solvent, such as water, acetone, mineral oil, or ethanol. Preferably, water is selected as the protic solvent.

[0039] Body 11 is soaked for an extended period of time, at least a day, preferably several days, or a week or more, depending on the size of body 11 and the desired protonated layer.

[0040] The body is shaped as a pellet, for example 0.7 mm thick, to form a mini-battery 20. The body is preferably pre-polished and has parallel faces.

[0041] Preferably, the liquid is heated to a certain temperature, for example 50° C., to speed up the process.

[0042] For LLZO-based compounds, the protonation equation with water is as follows: LLZO+H2O→HLLZO+LiOH

[0043] Regardless of the liquid used, protonated HLLZO compounds are obtained, which are weaker than the non-protonated LLZO compounds, which are very hard ceramics.

[0044] After this step, the body 11 has protonated layers 12, 13 around its periphery. The layers 12, 13 are deposited all around the periphery of the body 11 when the body is fully immersed in the liquid.

[0045] The layers have a thickness of, for example, 20 μm. The first layer 13 is deposited on a first side 7 of the body 11 and the second layer 12 is deposited on a second side 9 of the body 11 .

[0046] Optionally, method 10 includes a second step 2 of removing second protonated layer 12 from second side 9 of body 11 so that in the next step, positive electrode 15 can be directly laminated onto the non-protonated portion of body 11. This is because the conductivity between positive electrode 15 and the non-protonated portion is better than between positive electrode 15 and the protonated portion.

[0047] Preferably, the second removal step 2 includes polishing the second side 9 of the body 11. Polishing removes the protonated layer of material 12 and exposes the unprotonated portion of the body 11. For example, a 600 grit abrasive is used to remove the HLLZO-based protonated layer.

[0048] Alternatively, a second protonated layer 12 is carried on the second side 9 of the body 11 for laminating the positive electrode 15 thereon. Depending on the method of attachment of the positive electrode 15, and in particular the adhesive used, the second protonated layer 12 may be utilized.

[0049] In a third step 3, the body 11 is heated to a predetermined temperature in order to deprotonate the protonated layer 13. Deprotonation is understood to mean the removal of protons from the protonated layer 13. Above a certain temperature, the protons separate from the rest of the compound. The equation for deprotonation in protonated materials of the HLLZO system is: HLLZO→LZO+H2O

[0050] The predetermined temperature is preferably higher than 750° C. This minimum temperature allows the chemical reaction to proceed in the HLLZO-based protonated material. The deprotonated layer 13 becomes porous due to small cavities 18 resulting from the decomposition of the deprotonated layer 13. Nevertheless, the porous layer 13 maintains its hardness. The heating time is, for example, about 3 hours.

[0051] A fourth step 4 consists of depositing metal elements forming the negative electrode 14 on the protonated portion on the first side 7 of the body 11. The first side 7 is chosen to be opposite the second side 9 of the body 11. Thus, the negative electrode 14 is located on one side of the body 11 and the positive electrode 15 on the other side.

[0052] The metallic element includes a material selected from the following: - Alkali metals such as lithium, sodium, potassium, rubidium, cesium, or francium, - alkaline earth metals such as beryllium, magnesium, calcium, strontium, barium, or radium, - all transition metals from groups 3 to 11 of the periodic table, including the lanthanides and actinides, - Alloys of these metals.

[0053] The metallic element is preferably made entirely of this material.

[0054] Preferably, lithium is selected for its physical and chemical properties that lend themselves to use as the negative electrode 14 .

[0055] The molten metal element is deposited on the first deprotonated side 7 of the body 11. That is, the metal element is deposited in a molten state on the first side 7. In this state, the metal element adheres to the body 11 and penetrates into the cavities or cracks of the deprotonated layer 13, which has become porous. Because it is porous, the molten metal element easily penetrates into the deprotonated layer 13 from the first side 7.

[0056] In particular, this penetration of the metallic element into the porous layer 13 maximizes the surface area of ​​contact between the metallic element and the body 11, preventing the formation of undesirable dendrites.

[0057] The method includes a fifth step 5 of attaching a positive electrode 15 to a second side 9 of the body 11 opposite the negative electrode 14, which has not been protonated after the polishing performed in the second step 2.

[0058] For this purpose, a polymeric adhesive 16 is used to combine these, called the cathode liquid, so that the adhesive 16 becomes an ion conductor, allowing ions to pass through.

[0059] For example, a polymer adhesive 16 containing PEO-based polyethylene oxide, LiTFSi (lithium bis(trifluoromethanesulfonyl)imide)-based lithium salt, and THF (tetrahydrofuran) is used. The polymer adhesive 16 is dissolved in THF (tetrahydrofuran) and then laminated onto the second side 9, for example, using a drop-cast method. The THF is then dried, and the positive electrode 15 is laminated onto the polymer adhesive 16 such that the positive electrode 15 is permanently adhered to the second side 9.

[0060] The positive electrode 15 contains, for example, an active material selected from the following: - LiNi x Mn y Co z O2 or Li 2-x-y-z Ni x Mn y Co z Lithium nickel manganese cobalt oxide (NMC) such as O2, where x+y+z≦1, - LiNi 0.5 Mn 1.5 Lithium nickel manganese oxide (LNMO) such as O4, - Lithium iron phosphate (LFP) such as LiFePO4, - LMO-based lithium manganates such as LiMn2O4, and - NCA-based lithium nickel cobalt aluminum oxides such as LiNiCoAlO2.

[0061] The positive electrode 15 is preferably made predominantly from this material, in combination with a polymeric binder and carbon to improve their ionic and electronic conductivity.

[0062] Figure 2a) shows a body 11 made entirely of LLZO-based ceramic material. After a first protonation step, the body 11 comprises protonated layers 12, 13 around its periphery, as shown in figure 2b). The first layer 13 is disposed on a first side 7 of the body 11 and the second layer 12 is disposed on a second side 9 of the body 11.

[0063] The second side 9 of the body 11 is then polished so as to expose the unprotonated portion of this side, resulting in the body 11 in FIG. 2c) having an unprotonated portion on the second side 9 and a protonated layer 13 on the first side 7 of the body 11.

[0064] After the third deprotonation step, a porous deprotonated layer 13 is obtained beneath the unprotonated portion, as shown in Figure 2d. Small cavities 18 are generated in the deprotonated layer 13 during the deprotonation process.

[0065] According to a fourth step, the negative electrode 14 is formed by depositing molten metallic elements, preferably made of lithium, on the first deprotonated side 7 of the body 11, as shown in FIG. 2e).

[0066] The molten metal element penetrates the porous deprotonated layer 13, especially into the small cavities 18, so that the contact area between the negative electrode and the electrolyte 8 increases.

[0067] As shown in FIG. 2f), a positive electrode 15 is attached to the second, non-protonated side 9 of the body 11 using a polymer adhesive 16.

[0068] The battery 20 thus comprises an electrolyte 8 with an anode 14 on either side and a cathode 15 on the other side, and a body 11 having overlapping porous deprotonated ceramic layers 13 and unprotonated portions.

[0069] Such a battery 20 can be used in any electronic system, such as a watch, a drone, a mobile phone, a laptop computer, or an electric car, where the battery is of course of large size.

[0070] Of course, the invention is not limited to the embodiments described with reference to the figures, and alternatives are contemplated without departing from the scope of the invention. [Explanation of symbols]

[0071] 1. First Step 2. Second step 3. Third step 4. Fourth step 5. The Fifth Step 6. Sixth Step 7. First aspect 8 Solid electrolyte 9. The Second Aspect 10. Production methods for solid-state batteries 11 Main unit 12 Protonated Layer 13 Protonated Layer 14 Negative electrode 15 Positive electrode 16 Polymer Adhesives 18 Small cavity 19 Current Generator 20 batteries

Claims

1. A method (10) for producing a solid-state battery (20) having a solid electrolyte (8), comprising the following successive steps: - protonating a body (11) containing a protonatable ceramic material to form a protonated layer (12, 13) on said body (11); - a step (3) of deprotonating said protonated layer (13) so as to obtain a porous layer provided with small cavities (18), - depositing (4) metal elements forming the negative electrode (14) on said deprotonated layer on the first side (7) of said body (11) and allowing said metal elements to penetrate into said small cavities (18) of the porous layer; and - attaching (5) a positive electrode (15) to the second side (9) of said body (11); The method according to claim 1, further comprising:

2. The ceramic material is doped or undoped lithium and / or lanthanum zirconium oxides of the LLZO system, - doped or undoped β-alumina solid electrolyte materials, -Li 6 P.S. 5 X-based (X is selected from the elements Cl, Br, or I) or Li 2 S-P 2 S 5 sulfide-based solid electrolyte materials of the above type, -Li 3 M.X. 6 (M is a metal or a metal alloy, and X is a halogen) - Lithium ion conductive solid electrolyte materials based on LISICON (lithium superionic conductor), and - NASICON (sodium superionic conductor) based sodium ion conductive solid electrolyte material 2. The method (10) according to claim 1, characterized in that the material is selected from the group consisting of:

3. A method (10) according to claim 1 or 2, characterized in that in the protonation step (1), the body (11) is immersed in a protic solvent, such as water, acetone or ethanol.

4. A method (10) according to claim 1 or 2, characterized in that in the deprotonation step, the body (11) is heated to separate protons from the protonation layer (13).

5. 3. A method (10) according to claim 1 or 2, characterized in that said metal elements are melted onto said body (11) during said metal element deposition step (4).

6. The metal element is - the alkali metals lithium, sodium, potassium, rubidium, cesium or francium, - the alkaline earth metals beryllium, magnesium, calcium, strontium, barium or radium; - all the transition metals from groups 3 to 11 of the periodic table, including the lanthanides and actinides, and - Alloys of these metals 3. The method (10) according to claim 1 or 2, characterized in that it contains a substance selected from the group consisting of:

7. 3. The method (10) according to claim 1 or 2, characterized in that it comprises an additional step (2) of removing a portion of the protonated layer (12) from the body (11) in order to deposit the positive electrode (15) directly on the non-protonated part (11) of the body.

8. 8. The method (10) of claim 7, characterized in that the additional step (2) of removing a portion of the protonated layer from the body (11) is performed by polishing the second side (9) of the body (11).

9. The positive electrode (15) is - Lithium nickel manganese cobalt oxide of the NMC series, - lithium nickel manganese oxide of the LNMO series, - lithium iron phosphate of the LFP series, - LMO-based lithium manganates, and - NCA-based lithium nickel cobalt aluminum oxide 3. The method (10) according to claim 1 or 2, characterized in that it contains a material selected from:

Citation Information

Patent Citations

  • Solid electrolyte and secondary battery

    JP2013232284A

  • Stabilized solid garnet electrolyte and method

    JP2018502809A

  • Composite structure, lithium battery, and method for manufacturing composite structure

    JP2020077571A

  • System and method for treating the surface of a solid electrolyte

    JP2020516028A

  • Solid secondary battery

    JP2022148439A